ANALISIS FAKTOR PRODUKSI BAWANG MERAH LAHAN PASIR PANTAI DIKABUPATEN BANTUL - , Dina Aprilia ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Onion is one of the vegetable crops with the potential to be developed to support farmers' income. Tiron varieties can be classified as a special adapt to environments that are less productive, especially in the land of sand beach. This study aims to determine the knowing use of farm inputs onion, to determine the level of production and productivity of red onion, to determine the factors affecting onion production and analyze the magnitude of the onion farmers' incomes land Sanden sand beaches in the District, District and Sub Srandakan Kretek in Bantul. This study uses the analysis of the Cobb-Douglas production function with estimates obtained through regression analysis and transformed into natural logarithm form. The results of regression analysis of farm production function onion in the land of sand beaches indicates that the variable Urea, NPK and labor have a positive and significant impact on onion production. While the District Dummy Sanden insignificant which means do not differ with Sub Dummy Kretek Srandakan and showed significant results, which means that the production of sub Kretek higher than the District Srandakan. Differences by Sub District Kretek Srandakan can be seen from a different soil structure for the District of argillaceous sand and soil structure Pasiran Kretek for Srandakan District.